CODE MIXING IN DEDDY CORBUZIER’S PODCAST: A CASE STUDY OF SOCIOLINGUISTICS - Maimunah Ritonga; Amron Zarkasih Ritonga (JISOSEPOL: Jurnal Ilmu Sosial Ekonomi dan Politik, 2024)
This mixed-method research investigated the phenomenon of language mixing on Deddy Corbuzier Podcast entitled “Agnez Mo ... Mantantku Ter ....”. The podcast was obtained from Deddy Corbuzier’s YouTube Channel inform of video that further transcribed into the written conversation. The results showed that Deddy Corbuzier’s video podcast contained 124 occurrences of code-mixing. There were 5 types of code-mixing with different variations of appearance. Likewise, with the investigation of code-mixing functions, there are 6 functions with different percentages in each category. WEI was the most common type of code-mixing found. While F1 was the most function of why code-mixing was used by the speaker.